Transição do cuidado na alta hospitalar para o domicílio de pacientes recuperados de COVID-19 no contexto amazônico - ARRAIS, Diego João de Lima (Universidade Federal do Pará, 2023)
Introduction: The transition of care is characterized as the follow-up of patient care for the period of their hospitalization until the posteriority of this period, materializes the holistic care thoughts adopted by nursing and perpetuates the true meaning of "caring". Objective: To assess the transition of care for COVID-19 patients who were discharged from the hospital service to the home. Methodology: This is a quantitative, cross-sectional, descriptive and analytical study carried out with 49 patients and/or caregivers who were discharged from the Hospital Universitário João de Barros de Barreto, in Belém-PA. A random sample was used. The Care Transitions Measure-CTM-15 questionnaire validated in Brazil was applied. The collected data were tabulated in the Microsoft Office Excel® 2016 program, checked in full by another researcher to ensure the correct insertion of the answers and analyzed by the SPSS® software. Results: The mean score for care transition was 87.4 (±16.1). Factor 1 (Self-Management Training) had an average score of 82.6 (± 14.8), Factor 2 (Understanding of Medication) 86.6 (± 15.0), Factor 3 (Respected Preferences) 82.0 ( ± 16.7) and Factor 4 (Care Plan) 81.2 (± 18.2). Conclusion: The quality of the care transition perceived by the patient recovered from COVID-19, or by their caregivers, in the process of hospital discharge to home, was considered high, evidencing the involvement of the multidisciplinary team in the preparation and guidelines for the follow-up of care. at home, reducing the rates of readmissions and post-discharge complications.